The impact of climate changes on mass events in China. Issue 1 (2nd January 2016) - Wu, Haixiao
ABSTRACT: There is an increasing number of "mass events" in mainland China. My study extends the current studies to the context of China and tries to examine the potential impacts of climate changes on human conflicts in China. The results suggest a strong linkage between the deviation of monthly mean temperature from the historical mean and the number of mass events in a province. If the current trend of warming persists, in the next 6–8 decades, the number of mass events in China will increase by over 8.8%.